THE ROLE OF PUBLIC INSTITUTIONS TOWARD THE SUSTAINABLE TOURISM DEVELOPMENT STUDY CASE: ALBANIAN ALPS TOURISTIC REGION - BAJRAMI, Halil; FEJZA, Ejup; ISMAJLI, Ali (European Scientific Journal, ESJ, 2015)
Tourism today plays a big role in the development and sustainable growth. Its role is highlighted in the sustainability of economic development of the country. In the global economy, its role is increasingly being seen as a sector with multi-dimensional effects such as: economic, environmental and social effects. Kosovo, in terms of tourism resorts, has five touristic regions constituting an offer to diversify touristic resort market: competitive on the local and regional market. Albanian Alps Touristic Region (the case of this study), has significant advantages compared to other touristic regions of Kosovo in terms of tourism resources available for sustainable development of tourism. Current studies by local and international tourism institutions show the possibilities of tourism development in Kosovo, with a special emphasis on tourism region of Albanian Alps. Balkan yeasts include three countries: Kosovo, Albania, Montenegro. The potential in tourism in these three countries has been put at the service of regional tourism offer in the regional tourism market and beyond. Today, tourism is increasingly turning into a key sector of the economy to generate financial revenues and create opportunities for new jobs. One of many struggles faced by Kosovo’s tourism economy today is identifying a genuine strategy to develop the tourism product, and the use of marketing strategies that will orient towards sustainable tourism development. Thus, the aim of this study is to analyse the role of public institutions towards the sustainable growth through tourism. Public institutions, including ministries and municipalities responsible for tourism development in Kosovo are ten. Research was conducted in the period May to July 2014.